Choosing selective factors for the cultivation of Aerococcus viridans symbiont strains - D. O. Stepanskyi; I. P. Koshova; G. M. Kremenchutskyi; O. V. Khomiak (Regulatory Mechanisms in Biosystems, 2018)
Aerococci have certain cultivation characteristics. A well-known method of aerococcal cultivation uses indicator media which included the complex "oxolinic acid – etonium", but data indicating cases of conditionally pathogenic flora contamination due to the accumulation of microorganisms that are resistant to this complex have been obtained. Therefore, there was a need to search for new substances that would have a wide range of antagonistic activity in relation to the conditionally pathogenic flora and at the same time would not inhibit the growth of aerococci, and which would also be available and safe. The sensitivity of the A. viridans symbionts and conditionally pathogenic flora to the substances with antimicrobial activity of different groups was determined by the method of "wells". For research, A. viridans symbionts isolated from different microbiocenoses have been used. P. aeruginosa, S. aureus, K. pneumoniae, E. coli and C. albicans were used as conditionally pathogenic flora. Norfloxacin, pefloxacin, ofloxacin, gatifloxacin, levofloxacin, miramistin, decamethoxine, chlorhexidine, octenidine and boric acid were used as investigational drugs. Also, the optimal concentration of drugs which would suppress the growth of conditionally pathogenic flora, and would not show a negative effect on A. viridans was determined by serial dilutions. It was found that miramistin, norfloxacin and boric acid meet the necessary criteria. The serum dilutions method was used to determine the minimum inhibitory concentration (MIC) of these drugs in the experiment. Norfloxacin in a dosage of 12.5–50.0 μg/ml effectively inhibited the growth of the conditionally pathogenic flora, but also reduced the number of aerococci. The dose of 8.3 μg/ml met the criteria we needed, namely suppressing the growth of the conditionally pathogenic flora and not affecting aerococci. The concentration of miramistin and boric acid in a culture medium that showed a stong depressant effect on conditionally pathogenic flora and practically did not affect A. viridans was 50 μg/ml. In addition, miramistin and boric acid exhibited fungicidal action against C. albicans. Antimicrobial effects of the investigated drugs on the conditionally pathogenic flora was not complete in some cases, or inhibited the growth of aerococci at higher doses, so the effect of their rational combination on the conditionally pathogenic flora was investigated. As a result, an antimicrobial complex with optimal concentrations of substances (norfloxacin 8.3 μg/ml, myramistin 50 μg/ml, boric acid 50 μg/ml), which effectively suppresses UPMF and does not affect the growth of symbionic A. viridans, was determined. The specified antimicrobial complex can be used for the production of modified media for isolation, cultivation and study of biochemical activity of A. viridans microorganisms. Properties of aerococci, grown on the nutrient medium with the studied drugs did not differ from aerococci, grown on nutrient media without additives.